Optimizing Financial Planning for Retired Families to Support Financial Resilience - Winarni, Eko (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study discusses the optimization of financial planning for retired families to support financial resilience. The purpose of the study is to analyze the factors that contribute to the economic stability of retired families. The research method uses a quantitative approach with regression analysis and a qualitative approach through thematic analysis. The results of the study indicate that financial literacy, income diversification, and risk management strategies play an important role in maintaining financial balance. The conclusion of this study emphasizes the need for broader financial education for the community approaching retirement